The Role of Wearables in Chronic Disease Prevention and Health Promotion - Syam, Sadli; Arwan; Firmansyah; Anas, Adhe Sofyan; Alchamdani (Medicor : Journal of Health Informatics and Health Policy, 2025)
Wearable devices are gaining recognition as vital tools in preventive health monitoring, enabling a shift from reactive to proactive care models. This narrative review synthesizes evidence on the effectiveness of wearables in four key areas: cardiovascular health, diabetes management, general fitness, and elderly care. Findings indicate that wearable ECGs and blood pressure monitors improve early detection of cardiovascular risks and help reduce hospitalizations. Continuous glucose monitoring significantly enhances glycemic control, although access remains unequal between developed and developing countries. Fitness wearables increase physical activity, yet adoption is shaped by socioeconomic and cultural factors. Among elderly populations, wearable technologies support vital sign tracking and emergency detection, contributing to autonomy and safety, though challenges in digital literacy and affordability persist. Despite these benefits, several systemic barriers limit broader impact—particularly data privacy concerns, regulatory fragmentation, interoperability issues, and cost. Addressing these challenges requires integrated policy responses, user-centered design, and equitable access strategies. This review concludes that while wearable devices offer substantial potential for improving population health, realizing their impact depends on resolving critical access and infrastructure gaps, particularly in low-resource settings. Future research should prioritize longitudinal studies and culturally tailored innovations to enhance real-world effectiveness and global scalability.